Circolazione dei modelli e centri produttivi tra coroplastica architettonica e votiva. Riflessioni sulle teste femminili da Veio e dall’area ceretana alla luce di vecchi e nuovi dati. - Lo Verme, Chiara; Tulini, Carla (O T I V M, 2024)
The main focus of this paper is resuming the debate on the relationship between the votive coroplastic productions and the architectural ones, both from Veii’s and Caere’s territories. These important urban realities are two of the richest information sources of Southern Etruria about this kind of productions. The analysis’ starting point will be the in-depth examination of the votive and architectural iconographic models, based on terracotta heads and antefixes coming from Campetti, Portonaccio and Pyrgi sanctuaries between 6th and 4th century BC. Then, a cross-analysis of the data is provided to collect new information and to stimulate new questions about the spreading of iconographic ideals and models in Southern Etruria.